(untitled) (Global Journal of Management and Business Research, 2013)
Human resources development in the educational environment is becoming very critical to be able to provide quality and competitive graduates to the market. Education facility is the setting where interaction between students and teachers takes place. Facility quality affects students’ performance. The study was conducted using interviews and surveys to elecit data from 229 administers located at three directorates of the North Badia region. Subjects were selected using stratified random sampling. Results indicated that overall perceived performance was associated with the following entities of facility quality: natural ventilation, classroom arrangement flexibility, attention to furniture and equipment. Further, the following entities of facility quality were positively correlated with directorates of the North Badia Regions: additional lighting sources, natural ventilation, presence of rest rooms, and school size; and were negatively correlated with indoor sports facility.